e-Motion: Smart Remote Internet of Things Based Of Elderly Body Movements - Regina Nur Shabrina; Willy Nur Widiana; Nadya Sarah; R. W. Tri Hartono (Prosiding Industrial Research Workshop and National Seminar, 2021)
e-Motion: Smart Remote Internet of Things Based Of Elderly Body Movements